2000
DOI: 10.1128/jb.182.19.5606-5610.2000
|View full text |Cite
|
Sign up to set email alerts
|

Action of the Thiamine Antagonist Bacimethrin on Thiamine Biosynthesis

Abstract: Bacimethrin is an analog of the 4-amino-5-hydroxymethyl-2-methylpyrimidine (HMP) moiety of thiamine and inhibits the growth of Salmonella enterica serovar Typhimurium on a defined medium. Two classes of mutants that had increased bacimethrin resistance were isolated and characterized. Results showed that overexpression of the thi operon or specific lesions in thiD resulted in a bacimethrin-resistant phenotype. Phenotypic analyses of the thiD mutants suggested that they had a specific defect in one of the two k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
23
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 31 publications
0
23
0
Order By: Relevance
“…While it has been suggested that kibbled diets may increase thiamine requirements due to their high carbohydrate content14, recent literature suggests that thiamine concentrations in canned food may be below the recommended amounts for adult cats15. As for all mammals, thiamine cannot be synthesised by the cat, instead it relies on microbial de novo biosynthesis54 or ‘salvaging’ pathways545556.…”
Section: Resultsmentioning
confidence: 99%
“…While it has been suggested that kibbled diets may increase thiamine requirements due to their high carbohydrate content14, recent literature suggests that thiamine concentrations in canned food may be below the recommended amounts for adult cats15. As for all mammals, thiamine cannot be synthesised by the cat, instead it relies on microbial de novo biosynthesis54 or ‘salvaging’ pathways545556.…”
Section: Resultsmentioning
confidence: 99%
“…3 The toxicity of the bacimethrin on expression of thiamin biosynthetic genes was reported to be weak in comparison with the effect of thiamin itself. 2,5 An alternative explanation of bacimethrin toxicity was that upon conversion to MeOThDP, it could inhibit some or all of the ThDP-dependent enzymes in the cell. In experiments with Escherichia coli cells growing on minimal medium with bacimethrin and nutritional supplements, the OGDHc-ec, 1-deoxy- d -xylulose 5-phosphate synthase (DXPS), and transketolase were identified as major targets for inhibition by MeOThDP.…”
mentioning
confidence: 99%
“…A recent study demonstrated that the thiamin biosynthetic enzymes convert bacimethrin to 2Ј-methoxythiamin pyrophosphate (MeO-TPP), which inhibits thiamin-utilizing enzymes (13). In the presence of low levels of exogenous thiamin, cell growth is not inhibited by bacimethrin (14,15). CF 3 -HMP is converted by HMP-P kinase (ThiD) to CF 3 -HMP pyrophosphate (CF 3 -HMP-PP), which inhibits thiamin phosphate synthase (ThiE) (16).…”
mentioning
confidence: 99%